THE EFFECT OF COVID-19 ON MICRO SMALL AND MEDIUM ENTERPRISES CREATIVITY IN TANGERANG CITY - Mohamad Safii; Didi Sujadi (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The research method in this research is descriptive qualitative. Researchers collect, study and describe all the symptoms that occur due to COVID-19. The purpose of this research is to map the policies of the Tangerang city government in strengthening micro, small and medium enterprises. The results of this study are that efforts have been made to increase the income of micro, small and medium enterprises by providing training (capacity building), the approach taken is food safety, halal certification, the importance of certification and product quality and then empowerment programs.